Dynamics of Student Research at the Faculty of Economics and Islamic Business - Nilawati Nilawati; Rudi Aryanto; M Fachry Zaiman (UNIVED Press, 2023)
The purpose of this study is to examine the topics and methodologies used in the 2016–2019 student theses from UIN Raden Fatah Palembang's Faculty of Economics and Islamic Business. The descriptive qualitative research methodology is applied. According to this study, thesis research themes frequently combine research from different topics with an emphasis on Islamic economics and business; the most common theme is the Islamic banking system. The remaining portion relates to studies on waqf, alms, zakat, and infaq. Students typically employ influence analysis through statistical and comparative analysis as their research methodology. The number of research titles containing the terms